Evaluation of the Elder Abuse Training Program in Massachusetts, 1993-1995 - Holmes, William ([Verlag nicht ermittelbar], 1998)
These data were collected to evaluate the Elder Protection Project in Massachusetts, sponsored by the Massachusetts Attorney General's Office and funded by the Massachusetts Committee on Criminal Justice. The mission of the project was to train police officers to be aware of the changing demographics of the elderly population in Massachusetts and to communicate effectively and sensitively with senior adults so that officers could effectively intervene, report, and investigate instances of elder victimization, neglect, and financial exploitation. These data examine the quality of instruction given at the advanced training sessions conducted between September 1993 and May 1994 and offered in all regions of the state in coordination with local protective service agencies. Variables include the respondent's agency and job title, type of elder abuse programs offered by the agency, the respondent's estimate of the percentage of actual elder abuse reported in his/her area, and the respondent's opinion on the greatest obstacles to having elder abuse reported. Respondents rated their knowledge of elder abuse reporting laws, procedures for responding to elder abuse incidents, unique aspects of communicating with elderly people, and formal training on recognizing signs of elder abuse. Respondents that completed the two-day advanced law enforcement elder abuse training program rated the quality of the training and were also asked about issues related to elder abuse not covered in the training, names of new programs in the department or agency initiated as a result of the training, aspects of the training most useful and least useful, and suggestions regarding how the training program could be improved.